ADVERTISEMENT AND CONSUMERS’ PATRONAGE: EVIDENCE FROM TABLE WATER BRANDS IN OSUN STATE, NIGERIA - Kayode Muhammed IBRAHIM; Oluseyi AJAYI; Akintunde Aremu AKINTAYO; Dolapo Stephen Akinwumi (Malete Journal of Accounting and Finance)
This research examines advertisements and consumers’ patronage of selected table water brands in Osun State, Nigeria. The research concentrated on outdoor and radio advertising to appeal to consumer patronage. The study population was defined as infinite, and the sample size of 385 was estimated based on Cochran formula. Employing purposive sampling interest, data were gathered from 385 customers using structured questionnaires filled with close-ended questions. The study used multiple regression analysis. As for the outdoor advertising perception, the study established that the respondents had a low perception, with a mean of 2.92. The results of the regression analysis also showed that an overall impact on customer patronage was found to be 0.123 unstandardized Coefficient. This indicates that outdoor advertising, in particular, has a significant positive effect on customer patronage. This study also revealed that radio advertising has a higher positive perception, with a mean score of 4.13. In this study, the regression analysis indicated that radio advertising has a significant effect on customer patronage, as measured by an unstandardized coefficient of 0.043. This shows that radio advertising has a positive impact on customer patronage. The set of independent variables explained 87.2% of the total variation in customer patronage, indicating the usefulness of both types of advertising. The model was statistically significant, with a p-value of 0.000 and an F-value of 7.231. The research recommends that producers should ensure they employ multi-level advertising strategies, especially outdoor and radio advertising if customer patronage is to be improved.